Peranan Perpustakaan dalam Meningkatkan Minat Baca di SD Islam Khalifah Annizam Palembang - Sari, Maya Puspita; Ahyani, Nur; Nurlina, Nurlina (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Reading is one of the determining factors for educational success in a school. Reading ability is students' ability to understand the texts they read. One factor that influences this ability is interest in reading. To increase students' interest in reading, there needs to be a role for quality libraries, especially school libraries. This study aims to examine the role of the library in increasing students' reading interest at SD Islam Khalifah Annizam Palembang. Reading interest is a crucial aspect of students' academic and intellectual development. Using a descriptive qualitative research method with a case study approach, data were collected through observations, interviews, and documentation. The results indicate that the school library plays a significant role in enhancing students' reading interest. Various library programs such as scheduled reading times, storytelling activities, and a diverse and interesting book collection have successfully captured students' attention and increased their reading frequency. Additionally, support from teachers and parents also plays a role in creating a conducive environment for developing reading interest. The research results show that students' interest in reading is quite good, which can be seen from the programs and activities implemented by the library to increase their interest in reading. However, the role of libraries is not yet fully effective in increasing students' interest in reading, so improvements and optimization of library programs and activities are needed. In conclusion, the school library plays an essential role in increasing students' reading interest and should be continuously developed with innovative programs to support their academic achievement.